2011
DOI: 10.1002/cncr.26524
|View full text |Cite
|
Sign up to set email alerts
|

HIWI is associated with prognosis in patients with hepatocellular carcinoma after curative resection

Abstract: BACKGROUND: PIWI protein family was found to play an important role in stem cell self-renewal. Overexpression of HIWI, the human homolog of PIWI family proteins, was found in several solid tumors, although the role of HIWI in hepatocellular carcinoma (HCC) and its prognostic value remain unclear. METHODS: HIWI expression was measured in stepwise metastatic HCC cell lines (HCCLM3, MHCC97H, MHCC97L, SMMC7721, and HepG2), the normal liver cell line (L02), and HCC tissue samples (n ¼ 20). Proliferation and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 30 publications
0
97
1
Order By: Relevance
“…PIWI family proteins have been shown to be aberrantly expressed and associated with poor prognosis in ovarian, colorectal, gastric, hepatocellular, esophageal, and pancreatic cancers (13)(14)(15)(16)(17)(18), and piRNA expression has been observed in bladder, colon, lung, cervical, breast, hepatocellular, and gastric cancers (19)(20)(21)(22)(23)(24). Our recent study also identified a genetic variant in a mature piRNA sequence that is associated with breast cancer risk (25).…”
Section: Introductionmentioning
confidence: 67%
“…PIWI family proteins have been shown to be aberrantly expressed and associated with poor prognosis in ovarian, colorectal, gastric, hepatocellular, esophageal, and pancreatic cancers (13)(14)(15)(16)(17)(18), and piRNA expression has been observed in bladder, colon, lung, cervical, breast, hepatocellular, and gastric cancers (19)(20)(21)(22)(23)(24). Our recent study also identified a genetic variant in a mature piRNA sequence that is associated with breast cancer risk (25).…”
Section: Introductionmentioning
confidence: 67%
“…in addition to the function of HiWi as a potent growth regulator, another study revealed that low levels of expression of HIWI led to a significant decrease in the migration and invasion of hepatocellular carcinoma cells (16). The invasion of glioma cells into brain tissue is a pathologic hallmark of World Health organization (WHo) grade Ⅱ-Ⅳ gliomas, which contributes significantly to the failure of current treatments (28).…”
Section: Discussionmentioning
confidence: 99%
“…Small interfering rna against HiWi and a negative control (scrambled control) were purchased from genePharma (Shanghai, China). The following sirna sequences described previously (16) were used: HIWI, 5'-GCC guucauacaagacuaatt-3'; negative control, 5'-uuc uccgaacgugucacgutt-3'. transfection was performed using lipofectamine 2000 reagent (invitrogen life technologies, Carlsbad, CA, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time RT-PCR (RT-qPCR) was performed using a SYBR PrimeScript RT-qPCR Kit (TaKaRa Bio Inc., Tokyo, Japan) according to the kit mannual, with β-actin as an internal control. The primers for hiwi and β-actin were synthesized by Shanghai Sangon company (Shanghai, China) according to rhe reported sequences (Zhao et al, 2012). The RT-qPCR was performed with a Lightcycler 480 II (Roche, Mannheim, Germany).…”
Section: Rna Extraction and Quantitative Real-time Polymerase Chain Rmentioning
confidence: 99%